The gastrulation defective gene of Drosophila melanogaster is a member of the serine protease superfamily - Konrad, Kenneth D. (The National Academy of Sciences, 1998)
The establishment of dorsal–ventral polarity in the oocyte involves two sets of genes. One set belongs to the gurken-torpedo signaling pathway and affects the development of the egg chorion as well as the polarity of the embryo. The second set of genes affects only the dorsal–ventral polarity of the embryo but not the eggshell. gastrulation defective is one of the earliest acting of this second set of maternally required genes. We have cloned and characterized the gastrulation defective gene and determined that it encodes a protein structurally related to the serine protease superfamily, which also includes the Snake, Easter, and Nudel proteins. These data provide additional support for the involvement of a protease cascade in generating an asymmetric signal (i.e., asymmetric Spätzle activity) during establishment of dorsal–ventral polarity in the Drosophila embryo.